An integrated approach to predict genetic risk for Mosquito-Borne diseases in the local Population of Tehsil Haripur, Khyber Pakhtunkhwa, Pakistan - Rabea Basri; Muslim Bin Aqeel; Faryal Mehwish Awan; Sadiq Noor Khan; Ayesha Obaid; Rubina Parveen; Muhammad Mohsin; Wajeeha Akhtar; Abdal Hussain Shah; Tahira Sher Afghan; Amir Alam; Saira Khan; et al. (Scientific Reports)
Abstract Highly variable response shown by individuals against mosquito-borne infections suggests that host genetic factors play an important role in determining mosquito-borne disease onset. Therefore, it is necessary to determine the genetic risk of these diseases in specific populations. The current study aimed to determine the percentage of individuals in the general population carrying mosquito-borne disease susceptibility and protection-related variants. This study initially aggregated mosquito-borne disease susceptibility and protection-related variants from all publically available data and literature. Afterward, the allele frequency was calculated 1009 genetic variants of 366 genes associated with susceptibility and protection to estimate the global prevalence in multiple ethnicities (Middle Eastern, Ashkenazi Jewish, European (Non-Finnish), Latino/Admixed American, South Asian, East Asian, European (Finnish), North Asian, Southeast Asian, African American, and Swedish population). Furthermore, the cumulative allele frequency of all susceptibility and protection-related variants was calculated in diverse ethnic groups and the relationship with mosquito-borne disease-associated morbidity and mortality was examined to determine whether results are consistent with founder effect in these populations. Two prioritized genetic variants of IL-10 (rs1800871) and FcγRIIA (rs1801274) were examined in the Tehsil Haripur population to assess the genetic risks linked to susceptibility and protection against mosquito-borne diseases. The findings of this study revealed overlapping genes most implicated in mosquito-borne disease linked with susceptibility and protection across different ethnic ancestries. In the available sample size, the percentage of TC and TT genotypes in IL-10 genetic variant (rs1800871) was 12% and 88%, respectively and GA and GG genotypes in FcγRIIA (rs1801274) genetic variant were 6% and 94% respectively. Based on statistical analysis, the percentage allele frequency of IL-10 (rs1800871) variant was 0.2112% and the FcγRIIA (rs1801274) variant is 0.1128% in the current study. Additionally, this study reflects that screening of genetic variants associated with susceptibility and protection in a population gives better insights into organizing public health awareness campaigns to control diseases.